Removal of selected phthalates from aqueous solution by mesoporous-ordered carbon adsorbent - Katarzyna Jedynak; Dariusz Wideł; Jerzy Oszczudłowski (Adsorption Science & Technology)
In the present work adsorption of selected phthalates from the water samples on mesoporous carbon material was investigated. Carbon material was obtained by soft-templating method in the presence of citric acid. Adsorption process of phthalates was carried out from water solution using static method with sonication for process acceleration. Phthalates extraction from water phase, after adsorption on carbon material, was carried out using solid phase microextraction method. Extracted samples were analyzed using gas chromatography coupled with mass spectrometry method. Considering obtained experimental results it can be indicated that almost 100% of phthalates were adsorbed from water solutions. The efficiency of adsorption decreases with increasing molecular weight of phthalates.